The Role of the Six Thinking Hats in Enhancing Strategic Ambidexterity-A Field Study in Kirkuk Cement Factory - Dr. Modaffer Ahmed Hussein; Dr. Ahmed Abdullah Danook; Mohammed Hussein Jharbi (International Journal of Supply Chain Management, 2020)
Abstract The study aims to provide an integrated framework for the six thinking hats and strategic ambidexterity, which is one of the most important topics for business organizations to achieve the best in their performance, and to work on measuring the basic dimensions available to the organization. Therefore, Kirkuk Cement Factory was chosen as one of the important organizations in Iraq and which has a major role to raise the level of national industry, from here the problem of the study started, which was formulated with a set of questions aimed at identifying the most appropriate methods of exploiting the six hats to reach strategic ambidexterity. And determine the relationship and impact between the study variables, and to achieve this hypotheses were formulated, and an intentional sample consisting of a group of working individuals was selected, as their number reached (46) individuals, and the questionnaire form was used as a main tool to obtain basic information from the field side, and among the most important conclusions that the study found it is the great interest shown by the management of the organization concerned with the study in the dimensions of the six thinking hats and the dimensions of strategic ambidexterity to achieve a better competitive position.